Placing Students at the Heart of the Iron Triangle and the Interaction Equivalence Theorem Models. Issue 2 (23rd December 2014) - Lane, Andy
A number of visual models have been proposed to help explain the interplay and interactions between specified components of higher education systems at different levels and to take account of emerging trends towards open education systems. At sector and institutional levels the notion of an iron triangle has been posited, linking firstly access, quality and cost and latterly accessibility, quality and efficiency in order to suggest means for widening access to higher education for the same or lower cost without compromising outcomes. At the level of teaching and learning an interaction equivalence theorem was developed to explain the relative contributions to successful study of teachers, students and educational content in formal settings and which has recently been extended to informal settings. However both models deal mainly with the supply side of the educational systems they attempt to represent, namely impacts of the availability and accessibility to more people of the elements in the models, and largely ignore the demand side in terms of the affordability and acceptability of the available and accessible provision to students and learners alike. Further, while stimulating debate there has to date been limited empirical studies undertaken to validate both these models. Despite this lack of testing, this paper explores ways of extending these existing models both visually and conceptually by adding in the perspective of the prospective learner or student in respect to their organisational capacity to invest sufficient time for studying, the levels of preparedness and/or confidence that they hold before they engage in learning and the level of motivation for undertaking those studies. It is argued that these modified models provide a new contextual framework with which to examine the capacity of more open education systems at the national, institutional and individual learner level to be expanded effectively and equitably. It is hoped that these extended models provide a new basis for undertaking empirical studies to test out the underlying assumptions.